Ironweed - Kennedy, William, 1928- (New York : Penguin Books, 1984)
Chronicles the final wanderings of a one-time ballplayer turned down-and-out murderer.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Alcoholics -- Fiction; Family -- New York (State) -- Albany -- Fiction; Alcoholics -- Fiction; Family life -- Fiction; Albany (N.Y.) -- Fiction; Albany (N.Y.) -- Fiction